Efforts to Strengthen Cyber Defense and Cyber Security of the Indonesian Government in Maintaining National Security - Fadilah Munawaroh; Pujo Widodo; Yulian Azhari (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
The development of science and technology makes the threat to national defense also widen. From threats in the form of physical and non-physical. Increasingly sophisticated technology introduces people to the internet. Internet has become one of the primary needs today. Almost all activities are centralized from the Internet. Socio-economic, political, culture has been affected by the existence of the internet. Relations between communities have become very easy with the internet connected by social media. Out of a total of 270 million Indonesians, more than 170 million are active on social media. Not only that, economic activities, education to health have been facilitated by an online system with the existence of E-commerce and similar applications. This research discusses efforts to strengthen the Indonesian government's cyber defense and cyber security in maintaining national security. Using a descriptive qualitative research method, the author will discuss further the Indonesian government's efforts to strengthen cyber defense and security. One of these efforts has been carried out by issuing Government Regulation Number 71 of 2019 concerning the Implementation of Electronic Systems and Transactions, the existence of this PP strengthens the protection of personal data and information. Therefore it becomes interesting to be discussed further.